1999
DOI: 10.1093/heapol/14.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Unofficial Fees in Bangladesh: Price, Equity and Institutional Issues

Abstract: The widespread collection of unofficial fees at health facilities is a common form of rent-seeking behaviour in Bangladesh. Typically, unofficial fees come in the form of cash payments for the performance of required services, for direct purchase of drugs and medical-surgical requisites, and for service access. Using observational and interview methods, this study explores linkages between official and unofficial fees at three Bangladesh health facility levels; primary care Thana Health Complexes, secondary or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 1 publication
3
99
0
1
Order By: Relevance
“…80 The study has also found a similar scenario and one participant complained that after she got admitted to a hospital she had to pay extra money for proper service and another reported that a surgeon delayed her operation for ransom just before her delivery time.…”
Section: Financial Factorsmentioning
confidence: 69%
“…80 The study has also found a similar scenario and one participant complained that after she got admitted to a hospital she had to pay extra money for proper service and another reported that a surgeon delayed her operation for ransom just before her delivery time.…”
Section: Financial Factorsmentioning
confidence: 69%
“…One particularly disappointing observation made in the present study was that the costs of care from public health facilities in Bangladesh were high enough to require distress financing by many households, even though such facilities are heavily subsidized by the government. 32 This result indicates that health-care subsidization programmes in Bangladesh may not be working properly, especially among disadvantaged groups. One problem may be the inadequacy of the drugs and services available in public health facilities, which may be driving patients or their caregivers to purchase drugs and ancillary health services in the private market.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Rose-Ackerman argues that it is self-interest and greed that provoke individuals and groups to become involved in corruption. 19 Poor, salaried staff are vulnerable and easily bribed, but corrupt practices also serve the interests of highlevel off icials, 19 such as hospital administrators and doctors, who may not be directly involved.…”
Section: Discussionmentioning
confidence: 99%